Nonadherence to primary prophylaxis against Pneumocystis jirovecii pneumonia. - James D Heffelfinger; Andrew C Voetsch; Glenn V Nakamura; Patrick S Sullivan; A D McNaghten; Laurence Huang (PLoS ONE, 2009)
Despite the effectiveness of prophylaxis, Pneumocystis jirovecii pneumonia (PCP) continues to be the most common serious opportunistic infection among HIV-infected persons. We describe factors associated with nonadherence to primary PCP prophylaxis.We used 2000-2004 data from the Supplement to HIV/AIDS Surveillance (SHAS) project, a cross-sectional interview project of HIV-infected persons >or=18 years conducted in 18 states. We limited the analysis to persons who denied having prior PCP, reported having a current prescription to prevent PCP, and answered the question "In the past 30 days, how often were you able to take the PCP medication(s) exactly the way your doctor told you to take them?" We used multivariable logistic regression to describe factors associated with nonadherence. Of 1,666 subjects prescribed PCP prophylaxis, 305 (18.3%) were nonadherent. Persons were more likely to be nonadherent if they reported using marijuana (adjusted odds ratio [aOR] = 1.6, 95% confidence interval [CI] = 1.1-2.4), non-injection drugs other than marijuana (aOR = 1.5, 95% CI = 1.0-2.1), or injection drugs (aOR = 2.3, 95% CI = 1.3-4.1) in the past year; their mental health was "not good" for >or=1 day during the past month (aOR = 1.6, 95% CI = 1.2-2.2); their most recent CD4 count was <200 cells/microL (aOR = 1.6, 95% CI = 1.1-2.2); or taking ART usually (aOR = 9.6, 95% CI = 6.7-13.7) or sometimes/rarely/never (aOR = 18.4, 95% CI = 11.1-30.4), compared with always, as prescribed.Providers should inquire about and promote strategies to improve adherence to PCP prophylaxis, particularly among persons who use illicit drugs, have mental health issues, and who are not compliant with ART to reduce the occurrence of PCP.